Synergistic Effect of Banana Corm-Based Microbial Organic Liquid and Cyperus papyrus on Lead Removal in a Subsurface Flow Constructed Wetland System - Putu Primantari Vikana Suari; Nelson Darma Effendi; I Gede Andy Andhika Parahita (Tecno Scientifica Publishing, 2026)
Laboratory wastewater often contains hazardous heavy metals such as lead (Pb). A previous study found that laboratory wastewater contained Pb at a concentration of 3.52 mg/l, exceeding the Indonesian quality standard (1 mg/l; Minister of Environment Regulation No. 5/2014). In that study, laboratory wastewater was treated using a subsurface flow constructed wetland (SSF-CW) with Cyperus papyrus, which successfully reduced Pb concentration from 3.52 mg/l to 0.75 mg/l within 9 days. While effective, this setup required a long retention time and large space. To improve treatment efficiency, this study combined Cyperus papyrus with banana corm-based microbial organic liquid (MOL) containing indigenous microorganisms. A batch SSF-CW reactor (soil and gravel media) treated 1.2 l of artificial wastewater (initial Pb concentration: 3.33 mg/l) using 10% (v/v) banana corm MOL and four Cyperus papyrus plants. Pb concentration, pH, and plant morphology were monitored for nine days. The results showed that Pb concentration met the quality standard by day 2 (0.283 mg/l; 91.50% removal) and reached maximum removal on day 4, with Pb concentration < 0.0002 mg/l and 99.99% removal efficiency. Thus, combining Cyperus papyrus with banana corm MOL proved more effective in reducing Pb concentration than using Cyperus papyrus alone, achieving comparable results in only two days instead of nine.